A Phase 3 Study to Compare Delafloxacin With Moxifloxacin for the Treatment of Adults With Community-Acquired Bacterial Pneumonia (DEFINE-CABP) - Horcajada, Juan P (Open Forum Infect Dis, 2019)
BACKGROUND: The clinical and economic burden of community-acquired bacterial pneumonia (CABP) is significant and is anticipated to increase as the population ages and pathogens become more resistant. Delafloxacin is a fluoroquinolone antibiotic approved in the United States for the treatment of adults with acute bacterial skin and skin structure infections. Delafloxacin’s shape and charge profile uniquely impact its spectrum of activity and side effect profile. This phase 3 study compared the efficacy and safety of delafloxacin with moxifloxacin for the treatment of CABP. METHODS: A randomized, double-blind, comparator-controlled, multicenter, global phase 3 study compared the efficacy and safety of delafloxacin 300 mg twice daily or moxifloxacin 400 mg once daily in adults with CABP. The primary end point was early clinical response (ECR), defined as improvement at 96 (±24) hours after the first dose of study drug. Clinical response at test of cure (TOC) and microbiologic response were also assessed. RESULTS: In the intent-to-treat analysis population (ITT), ECR rates were 88.9% in the delafloxacin group and 89.0% in the moxifloxacin group. Noninferiority of delafloxacin compared with moxifloxacin was demonstrated. At TOC in the ITT population, the success rates were similar between groups. Treatment-emergent adverse events that were considered at least possibly related to the study drug occurred in 65 subjects (15.2%) in the delafloxacin group and 54 (12.6%) in the moxifloxacin group. CONCLUSIONS: Intravenous/oral delafloxacin monotherapy is effective and well tolerated in the treatment of adults with CABP, providing coverage for Gram-positive, Gram-negative, and atypical pathogens. CLINICALTRIALS.GOV IDENTIFIER: NCT03534622.